Improvements in smoothness of chewing cycles in adults with mandibular prognathism after surgery: a longitudinal study. (16th March 2013) - Yashiro, K.; Takada, K.
Summary Although adults with mandibular prognathism are known to show impaired smoothness of masticatory jaw movements, it remains uncertain whether/how the surgical‐orthodontic treatment is effective to improve masticatory jaw movements. The aims of this study were (i) to verify whether the surgical‐orthodontic treatment of patients with mandibular prognathism improve smoothness of the chewing jaw movements post‐operatively and, if so, (ii) to examine whether the improved parameters show similar quantities as those of the control subjects. The chewing jaw movements for 13 patients with mandibular prognathism were recorded at pre‐ and post‐treatment stages. The patient group was divided into two groups: Class IIIclosed showed full occlusal contact at the habitual intercuspal position, whereas Class IIIopen showed inability of occlusal contact between the upper and lower anterior teeth. The control group (CG) consisted of 52 subjects having acceptably good occlusion. The normalised jerk cost (NJC), movement duration and peak velocity in jaw closing were compared. For both Class IIIopen and Class IIIclosed groups, statistical comparisons revealed that the NJC and movement duration were decreased after the treatment, whereas the peak velocity was increased (all P < 0·01). For the Class IIIopen, these quantities at the post‐treatment stage did not show any significant differences compared with those for the CG. It is concluded that the smoothness of chewing jaw movements for patient with mandibular prognathism were improved after treatment, and for the patients with anterior open bite at pre‐treatment, the post‐operatively achieved smoothness of jaw‐closing movements did not differ from those of the CG.